China–Global Relations: A Higher Education Cold War? - Wang, Lizhou; Wen, Wen (International Higher Education, 2021)
In 2020, as the discourse and initiatives of “decoupling” or “the new Cold War” deteriorate between the United States and China, higher education invariably comes under fire owing to its international nature. Higher education is premised on the existence of open and free global movements and exchanges to enable institutions and individuals to generate scientific production. How higher education holds its ground during these times of geopolitical turmoil is a question vital to its future.